A Hister Beetle Carcinops pumilio (Erichson) (Insecta: Coleoptera: Histeridae: Dendrophilinae: Paromalini) - Matthew R. Moore; Phillip E. Kaufman (EDIS)
Includes: Introduction - Taxonomy and Synonymy - Distribution - Description - Life Cycle - Ecology - Economic Importance - Medical and Veterinary Importance - Selected References